Por uma moradia termicamente confortável: proposta de habitação de interesse social com ênfase no conforto térmico - Monteiro, Verner Max Liger de Mello (2012)
This research covers the topic of social housing and its relation to thermal comfort, so applied to an architectural and urban intervention in land situated in central urban area of Macaíba/RN, Brazil. Reflecting on the role of design and use of alternative building materials in the search for better performance is one of its main goals. The hypothesis is that by changing design parameters and choice of materials, it is possible to achieve better thermal performance results. Thus, we performed computer simulations of thermal performance and natural ventilation using computational fluid dynamics or CFD (Computational Fluid Dynamics). The presentation of the thermal simulation followed the methodology proposed in the dissertation Negreiros (2010), which aims to find the percentage of the amount of hours of comfort obtained throughout the year, while data analysis was made of natural ventilation from images generated by the images extracted from the CFD. From model building designed, was fitted an analytical framework that results in a comparison between three different proposals for dwellings housing model, which is evaluated the question of the thermal performance of buildings, and also deals with the spatial variables design, construction materials and costs. It is concluded that the final report confirmed the general hypotheses set at the start of the study, it was possible to quantify the results and identify the importance of design and construction materials are equivalent, and that, if combined, lead to gains in thermal performance potential.